The effect of statin therapy in stroke outcome: A double blind clinical trial - Mohammad Zare; Mohammad Saadatnia; Seyed Ali Mousavi; Kiandokht Keyhanian; Vahid Davoudi; Esmaeil Khanmohammadi (International Journal of Preventive Medicine, 2012)
Background: Through a clinical trial we evaluated statin therapy benefits over stroke outcome. Methods: All patients with moderate stroke in Middle Cerebral Artery (MCA) were registered during February 2006 to February 2008, in Al Zahra Hospital, Isfahan, Iran. Among 55 patients who were enrolled in the present study, 25 subjects received 20 mg lovastatin daily, for 90 days after stroke attack (group 1) and 30 patients received no treatment (group 2). Patients were assessed at admission, 7 and 90 days after stroke. National Institutes of Health Stroke Scale (NIHSS) score was recorded in the day 1 and 7 in the hospital with a questionnaire and BARTHEL index was estimated 90 days after stroke incidence by a telephone survey or in an outpatient visit. Data were analyzed by means of c2 , ′t′ test and Independent ′t′ test. Results: NIHSS score measured in first day immediately after stroke attack and following 7 days, did not differ significantly in two groups. Moreover, BARTHEL index recorded within 90 days was not also different comparing group 1 and 2. After 90 days, no mortality was recorded in group 2, while one patient expired in group treating with statins (P-value>0.05). Discussion: We did not find statins administration to play any role in stroke recovery and consequent long-term prognosis. More researches with larger samples are needed to establish the possible favorable outcome of statins when administered in cerebrovascular diseases.